Fusion of Normoxic- and Hypoxic-Preconditioned Myoblasts Leads to Increased Hypertrophy - Tamara Pircher; Henning Wackerhage; Elif Akova; Wolfgang Böcker; Attila Aszodi; Maximilian M. Saller (Cells, 2022)
Injuries, high altitude, and endurance exercise lead to hypoxic conditions in skeletal muscle and sometimes to hypoxia-induced local tissue damage. Thus, regenerative myoblasts/satellite cells are exposed to different levels and durations of partial oxygen pressure depending on the spatial distance from the blood vessels. To date, it is unclear how hypoxia affects myoblasts proliferation, differentiation, and particularly fusion with normoxic myoblasts. To study this, we investigated how 21% and 2% oxygen affects C2C12 myoblast morphology, proliferation, and myogenic differentiation and evaluated the fusion of normoxic- or hypoxic-preconditioned C2C12 cells in 21% or 2% oxygen in vitro. Out data show that the long-term hypoxic culture condition does not affect the proliferation of C2C12 cells but leads to rounder cells and reduced myotube formation when compared with myoblasts exposed to normoxia. However, when normoxic- and hypoxic-preconditioned myoblasts were differentiated together, the resultant myotubes were significantly larger than the control myotubes. Whole transcriptome sequencing analysis revealed several novel candidate genes that are differentially regulated during the differentiation under normoxia and hypoxia in mixed culture conditions and may thus be involved in the increase in myotube size. Taken together, oxygen-dependent adaption and interaction of myoblasts may represent a novel approach for the development of innovative therapeutic targets.